PENGARUH KUALITAS PELAYANAN DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK BADAN DI KPP PRATAMA MEDAN BELAWAN - Syamsul Bahri Arifin; Aulia Arief Nasution (Universitas Medan Area, 2017)
The effort to optimize tax revenues are not reliable from the role of the Direktorat Jendral Pajak (DJP) alone but it takes an active role of all Indonesian people, especially taxpayers. Taxation conditions that require the active participation of taxpayers in carrying out taxation requires compliance with high taxpayers, namely compliance in the fulfillment of tax obligations in accordance with the provisions of the Law Taxation. The purpose of this study is to examine the effect of service quality and tax sanctions on taxpayer compliance in KPP Pratama Medan Belawan. The population of this study is the corporate taxpayer who reported the SPT and Annual SPT in the area of KPP Pratama Medan Belawan, North Sumatra.Kemudian conducted sampling of 100 respondents used in this study. This research method using multiple linear regression analysis. The results of this study indicate that Service Quality and Tax Sanction have a significant effect, either partially or simultaneously to Taxpayer Compliance Agency In KPP Pratama Medan Belawan ..Keywords: Service Quality, Tax Sanction and Taxpayer Compliance.